Tourism in rural Bangladesh: Unlocking opportunities for poverty alleviation? - Islam, Faridul; Carlsen, Jack (Centre for Tourism Research and Development, 2012)
The purpose of this paper is to investigate the nexus between tourism development and the alleviation of poverty in the context of rural Bangladesh. Three quarters of the population of Bangladesh live in rural areas where poverty levels, as measured by income and calorie intake, are extreme. Forms of tourism that maximize benefits for the poor through providing opportunities for income and employment generation are explored. However, a number of barriers exist for poverty alleviation through tourism, including inadequate support from government, nongovernment and financial organizations, dominance of tourism by intermediaries and wealthy elites, lack of awareness and/or ability of traditional farming communities to participate in tourism opportunities and inadequate training and technical support. A single embedded case study involving government, tourism industry and non-government organizations (NGOs) in Bangladesh investigates these barriers. The potential for tourism-related micro-enterprises is then discussed as well as the need for industry, government and NGOs to work with micro-credit organizations to unlock opportunities for poverty alleviation through tourism in rural Bangladesh.